g-ANGLE BETWEEN A LINE AND A SUBSPACE AND BETWEEN TWO PLANES IN AN n-NORMED SPACE - Nur, Muh.
This dissertation discusses the angle between two subspaces in an inner product space and in a normed space, and its generalization in an n-inner product space and in an n-normed space for n 2: In the discussion of angle in a normed space, it is formulated the g-angle and the gg-angle between two vectors and their connection. Moreover, we formulate the g-angle between a 1-dimensional subspace and arbitrary dimensional subspaces. In this section, we also discuss the g-angle between 2-dimensional subspaces. The next section of this dissertation discusses the angle in an n-inner product space and the angle in an n-normed space for n 2: The method used is utilizing the result of a new inner product derived from an n-inner product and the angle in an inner product space. Likewise, using a new norm that is derived from an n-norm and the g-angle in a normed space, we study the g-angle in an n-normed space